Mechanical response characteristics of full depth reclaimed pavement based on 3D-move model - Haiwei Zhang; Ning Liu; Bowei Sun; Qingqing Zhang; Jiazhen Liu (PLoS ONE, 2025)
The mechanical properties of full-depth reclamation of pavements with Portland cement (FDR-PC) provide a theoretical basis for seeking the structural design of reclaimed pavements and selecting specific technical solutions. Relying on the typical reclaimed pavement structure, this paper applies 3D-Move Analysis to construct a numerical model of full-depth reclaimed pavement. It dynamically analyzes the mechanical properties of FDR-PC in four aspects: plane, spatial, speed, and temperature. The study shows that: in the plane direction, only the mechanical response at the center of the wheel track can be investigated; the maximum vertical strain along the depth direction from the road surface to the top of the residual layer occurs at the top of the residual layer of the old road; the speed is within a certain range, and the faster the vehicle travels, the smaller the influence on the mechanical response; when the temperature increases, the individual mechanical response increases to different degrees.